Consuming Canada: How fashion firms leverage the landscape to create and communicate brand identities, distinction and values. Issue 90 (March 2018) - Brydges, Taylor; Hracs, Brian J.
Highlights: Integrates economic and cultural geography perspectives on the landscape. Nuances our theoretical understanding of spatial entanglements and place-branding. Contributes to nascent examinations of social media and visual data. Demonstrates how fashion firms leverage the landscape to create values. Presents an original analysis of Canada's fashion marketplace in the digital age. Abstract: In the increasingly global and competitive fashion industry, firms are adopting a variety of strategies to generate value and brand loyalty. While some emphasise the quality of material elements such as inputs, local production and design, others focus on immaterial aspects such symbolic value and exclusivity. In recent years, place-branding has become an important way to create connections between people, places, and products. Yet, the processes behind this type of branding remain poorly understood. In particular, limited attention has been paid to the ways in which landscapes – in all their forms – are being incorporated into place-branding practices. Drawing on 87 interviews, participant observation and an innovative analysis of Instagram accounts, this paper examines how a range of Canadian fashion firms leverage the landscape to create and communicate brand identities, distinction and values. It demonstrates how firms of different sizes and scales construct, harness, or reimagine landscapes and/or popular stereotypes to connect with Canadian identities and consumers. It also highlights how landscape-centric branding can be combined with broader value creation strategies such as local production. In so doing, this paper brings together the economic geography literature on place branding and the cultural geography literature on landscape and identity, and makes a methodological contribution to nascent examinations of social media and visual data sources in geography.